Financial Literacy and Demographic Effect on Investor Investment Decisions - Malini, Helma (Jurnal Doktor Manajemen (JDM), 2024)
This research seeks to determine the impact of financial literacy, age, income, and ethnicity on overconfidence and investment decisions in three major cities in Indonesia. This study employs quantitative research techniques of the associative variety. This study's participants resided in three major cities in Indonesia and had invested in equities. One hundred investors in Jakarta, Bandung, and Surabaya were selected as sample respondents using a technique of purposive sampling, yielding a sample size of 100. The respondent is at least 20 years old and has invested in equities for at least a year on the capital market. Results indicated that financial literacy, income, and semester had a positive effect on overconfidence, whereas age and ethnicity did not. Age, income, and ethnicity have no positive effect on investment decisions, whereas financial literacy does. Investment decisions are positively affected by overconfidence.